Problems of the water management of cross-border Selenga River Basin - B. O. Gomboev (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
The article deals with the problems of the state management and protection of Selenga River Basin Selenga, the main tributary of the lake Baikal located in the territory of the Russian Federation and Mongolia. On the ground of the data transfer of pollutants from the Selenga River flow and analysis of legal documents it is identified the main problems of cross-border region’s management.